ISTISHLAH DAN APLIKASINYA DALAM PENETAPAN HUKUM ISLAM - Asiah, Nur (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
In essence, all the laws that have been established by God Almighty it has benefits because all legal aspects either the command or prohibition provides benefits in human beings. However, when humans find a problem that does not have sharih argument,then benefit consideration and prevention of damages becomes urgent in law enforcement.In its application as evidence, scholars are divided into two groups: first, scholars who received istishlah as evidence under the condition that the beneficiaries is essential and it is not the alleged beneficiaries, it is general, personal, and it is not contrary to the arguments of syaraâ.Secondly, scholars who deny the application of istishlah as evidence in establishing Islamic law.